(untitled) (Journal of Information Technology and Digital World, 2022)
The data surge caused by the increase in the use of IoT devices in our day-to-day activities requires careful storage and maintenance systems to ensure the protection and integrity of private information. Users are provided with prospects to use rule-based programs and services that can be interconnected with their devices thereby enabling automation in the prodigious IoT ecosystem. The sensitive IoT data is generally stored and processed in cloud services. This data may be vulnerable to several threats. It is crucial to protect rule-based programs and sensitive IoT information against cyberattacks. The rule-based program and IoT data integrity and confidentiality can be maintained with the help of the framework proposed in this work. An end-to-end data encryption model based on advanced encryption standard and Intel SGX are used to design the framework of the data privacy preservation model. Real as well as simulated IoT device data are used for securely executing the rule-based programs in the SGX to evaluate the proposed framework.